Expanding the literature on job satisfaction in corrections: a national study of jail employees - Stinchcomb, Jeanne B. (Criminal justice and behavior, 2013)
While few variables have been studied with greater frequency than job satisfaction, outcomes have largely reflected ambiguous and inconsistent findings. To advance empirical knowledge as it relates to job satisfaction in corrections, this research design addresses a number of shortcomings prevalent in extant correctional literature. In that regard, it uniquely focuses on the rarely explored work environment of jails in the United States, incorporates a nationwide target population, includes both personal and organizational variables in the analysis, and employs a multifaceted inferential methodology based on the strength of causal analysis. Results indicate that it is not the personal variables such as age, race, gender, or ethnicity that primarily account for the job satisfaction of jail line staff, but rather, organizational variables. These include a supportive work climate, empowerment/autonomy, and compensation/benefits, with the greatest contributor being the employee?s overall work environment. Implications of the findings for sheriffs and jail administrators committed to the long-term process of elevating employee job satisfaction are discussed.